Numerical investigation on the relationship between human thermal comfort and thermal balance under radiant cooling system - Gao, S. (2018)
The radiant air conditioning system, possessing the characteristics of draft less and small temperature gradients in the occupied zone, is becoming increasingly attractive in recent years, due to its advantage of providing more comfortable indoor environment with low energy consumption against the conventional convective air conditioning system. In order to master the features of the radiant air conditioning system and improve its design process, the interrelation among the human thermal comfort and the heat exchange between human body and its surroundings subject to the radiant air conditioning system is investigated in this paper. Based on Fanger's thermal comfort model, the PMV (Predicted Mean Vote) is used to evaluate the human thermal comfort. To calculate the heat loss from human body, the human thermal balance and heat release characteristics under radiant cooling system are discussed in detail. The CFD model in terms of different cooling ceiling temperatures and air supply temperatures is simulated and analyzed by Airpak. The relationship between the heat loss from human body and thermal comfort is achieved based on the simplified formula for the heat loss and the PMV value obtained from numerical results. For human body under radiant air conditioning system, numerical results showed that the sensible heat loss from human body is approximately linear to the PMV under all simulated conditions. The simplified PMV model, directly from the respect of human heat balance instead of complicated environmental parameters, is finally proposed.